Management of Decision Making in Improving the Quality of Education at MTsN Kota Solok - Jamilus Jamilus (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
This study aims to describe the management of decision making in improving the quality of education at MTsN Kota Solok. The quality of education can be seen from three aspects, namely: input, process and output. This research uses descriptive qualitative method. The results of this study indicate that the planning for decision making by the Head of MTsN Kota Solok is carried out through a meeting forum involving the entire assembly of teachers and employees by identifying the needs of the institution. Organizing decision making is done by classifying problems that require decision making based on a priority scale. The implementation of decision making is carried out according to the plan, namely through a meeting forum attended by the entire assembly of teachers and employees. In the meeting, the teachers and employees were asked for their opinions and suggestions related to the problems that were taken and then mutually agreed upon. Decision-making control is carried out through monitoring and evaluation as well as supervision and follow-up plans.